A healthcare quality management system underpinning the 3-E model and its application in a new tertiary hospital in Australia - Qun (Catherine); Greg Sweetman, MBBS DipRACOG DA (UK) (Elsevier, 2017)
Objectives: Engaging, enhancing and embedding clinical audit improvement activities into everyday practice to develop capacity, capability and culture in continuous improvement. Method: Through the implementation of an electronic quality management system called Governance, Evidence, Knowledge and Outcome (GEKO), the key aspects of governance, evidence knowledge and outcomes were able to be applied to quality initiatives. Implementation of the GEKO system incorporated the principles of total quality control and management to include strategic management control and marketing in parallel with leadership strategies. The vision was to motivate staff to enable ownership of the quality cycle of continuous improvement of patient care to incorporate underlying systems and processes that impact on patient care. Results: A continuous improvement pathway was successfully established 4 months post hospital commissioning. Over 890 (approximately 16% workforce) multidisciplinary and multi-professional staff received training and support for QIs in 12 months; over 535 quality proposals were received on GEKO. Submissions by profession: nursing and midwifery 46% (246), medical 33% (177), allied health 9% (48), pharmacy 5% (27), and non-clinical staff 7% (37). Average new submissions per month were 42. Reviews demonstrated the application of a rapid cycle approach to develop, test, modify and refine improvements and enhanced clinical care. Conclusion: Appropriate governance structure, processes, extensive education and training together with collaborative relationships are the keys to embed clinical audit improvement into everyday practice. The availability of a quality management system like GEKO is very useful to make QI accessible to all staff.